2012
DOI: 10.1038/ncomms2064
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Wnt signalling in human embryonic stem cells generates an equilibrium of distinct lineage-specified progenitors

Abstract: The pluripotent nature of human embryonic stem cells (hESCs) makes them convenient for deriving therapeutically relevant cells. Here we show using Wnt reporter hESC lines that the cells are heterogeneous with respect to endogenous Wnt signalling activity. Moreover, the level of Wnt signalling activity in individual cells correlates with differences in clonogenic potential and lineage-specific differentiation propensity. The addition of Wnt protein or, conversely, a small-molecule Wnt inhibitor (IWP2) reduces h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
176
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(199 citation statements)
references
References 35 publications
18
176
5
Order By: Relevance
“…In pre-gastrula amphibian embryos, evidence for establishment of a neural boundary via planar signaling was reported (Savage and Phillips, 1989;Zhang and Jacobson, 1993). A recent study in amphibians proposes a shared genetic regulatory network of blastula pluripotent cells with developing NC cells at the neural border (Buitrago-Delgado et al, 2015). These studies in avian and amphibian embryos hint at an early fate specification for NC.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In pre-gastrula amphibian embryos, evidence for establishment of a neural boundary via planar signaling was reported (Savage and Phillips, 1989;Zhang and Jacobson, 1993). A recent study in amphibians proposes a shared genetic regulatory network of blastula pluripotent cells with developing NC cells at the neural border (Buitrago-Delgado et al, 2015). These studies in avian and amphibian embryos hint at an early fate specification for NC.…”
Section: Introductionmentioning
confidence: 83%
“…The exact embryonic equivalent of ESCs in humans, however, is still under debate. hESCs appear to display low but heterogeneous endogenous WNT activity (Blauwkamp et al, 2012;Davidson et al, 2012). The absolute requirement of WNT activity in hESC renewal is contested but it appears that nuclear β-catenin signaling is dispensable for ESC maintenance (Kim et al, 2013) and WNT activation leads to differentiation of hESCs (Davidson et al, 2012;Dravid et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these seemingly opposing differences can be attributed to differences between human and mouse ES cells, relative differences in levels of Wnt signaling are well known to affect cell fate outcome and could be a contributing factor (for review, see Merrill 2012). In this regard, it was recently reported that within human ES cell (hESC) populations, some cells are more Wnt-sensitive than others, and, upon differentiation, the Wnt(high) hESCs predominantly form endodermal and cardiac cells, whereas the Wnt(low) hESCs generate primarily neuroectodermal cells (Blauwkamp et al 2012). Similarly, short-term treatment of the GSK3b inhibitor BIO or soluble Wnt3a protein has been shown to stimulate ES cell self-renewal and maintain pluripotency, while longterm treatment of ES cells with Wnt3a reduces their selfrenewing capacity and leads to differentiation.…”
Section: How Receiving Stem Cells Perceive External Wnt Cuesmentioning
confidence: 99%
“…However, this phenomenon appears to be transitory in many lines and, in some instances, can be erased by additional reprogramming, by chromatin-modifying drugs, or with extended passaging of the cells (34). Differences in endogenous signalling activity may also contribute to the heterogeneity of iPSC lines generated from the same tissue sample (35). A recent study on variation between pluripotent cell lines indicates that a difference in genetic background is the major factor for variation, rather than aberrations arising during viral transfection (36).…”
Section: Ips and Es Cells How Similar Are They?mentioning
confidence: 99%
“…During embryogenesis, Nodal and Wnt signalling triggers endoderm development. Later on in the differentiation process, the switching on or off of this signalling regulates endodermal tube patterning (34,35). Mesodermal cells surrounding the endoderm tube are involved in the hepatic commitment of foregut cells (mainly through fibroblast growth factor and bone morphogenetic protein signalling) and liver bud formation.…”
Section: Generating Hepatocytes From Ips Cellsmentioning
confidence: 99%